LANGUAGE ACQUISITION IN BAHASA INDONESIA: A CASE STUDY ON 4.2 AND 1.8-YEAR-OLD CHILDREN - Hepnyi Samosir (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims at tracing the first language acquisition of two children at age of 4.2 and 1.8. This study is conducted based on naturalistic observations. The method used is the descriptive qualitative method. The observation is carried out by recording the activity of the subjects (Octa – 4.2 years old, and her sister, Adek – 1.8 years old) using a camcorder and also making hand writing. The recording consists of natural and spontaneous conversation among the two children and their father. The result of the study presents that a 4.2-year -old) child seems to be able to use sentences having grammatical features corresponding to adult language and master declarative, negative, imperative, interrogative sentences, but the type of the clauses used is limited to the simple sentences. An 1.8-year-old child seems to be able to use single words to express idea but utters some words imperfectly. She omits a first consonants such as /h/, or even vowel of a particular word; reduplicate syllables; and substitute consonants /c/ with /t/, consonant /s/ with consonant /h/. It is not expected that an one year, eight months to be able to accurately produce the /r/ sound because it may be pronounced /l/.